ANALISIS PENINGKATAN GERAK DASAR DALAM PERMAINAN KASTI - Muhammad Deden Syaifulloh; Rachmi Marsheilla Aguss (Journal of Arts and Education, 2021)
As we know basic movements are simple movements such as walking, running, throwing, jumping. In this study, there were a few difficulties as a result of the covid-19 pandemic that had not ended and made lectures that should be offline become online, for sports education students at the Indonesian Technocrat University it was difficult to study lectures that should have been practiced online, such as small game lectures, for example, the new one. several times face to face. This study aims to determine the effort of motion in baseball games for sports education students at the Indonesian Technocrat University by throwing, catching and hitting the ball, whether the learning outcomes carried out are in accordance with what is expected, therefore the researcher describes the evaluation results obtained from sports education students with a total of 20 people consisting of 16 boys and 4 girls with the results using tables to facilitate the search for average data and the results of learning success in research stage 1 there are 98% results for the average student who can throw the ball then stage 2 is catching the ball there are results of 60% meaning it is quite good and stage 3, namely hitting the ball, there are 26% results. This result is very far from the success of learning outcomes. It can be concluded from the evaluation results that students still have many difficulties when hitting the ball, meaning that the basic motion goals that can be evaluated must emphasize students to be more active in hitting ball exercises and often to evaluate.